ANALISIS GAYA BELAJAR SISWA BERBAKAT SD IT PERGURUAN BAITI JANNATI - Sinta; Dara Fitrah Dwi; Abdul Mujib; Arrini Shabrina Anshor (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was conducted at SD IT Perguruan Baiti Jannati on students in grade IV consisting of 7 students with 5 academically gifted students and 2 non-academic gifted students. In grade V students also consisted of 7 students with 5 academically gifted students, 1 non-academic gifted student and 1 academically and non-academic gifted student at SD IT Baiti Jannati with the aim of analyzing the learning styles of gifted students both in academic and non-academic fields. Data were obtained through questionnaires, observations, and interviews with students and teachers. Data were analyzed using a qualitative approach with a data reduction model, data presentation, and conclusion drawing. The results of the research conducted at SD IT Perguruan Baiti Jannati showed that the dominant learning style in grade IV is visual, because students prefer to learn by reading, writing, and viewing displays such as in games. The most dominant learning style in grade V is visual and kinesthetic, because students find it easier to understand material through direct activities, practice, play, and using aids. In addition, it was found that gifted students both academically and non-academically show uniqueness in the way they absorb information